Voices of Thai Patients With Non-Communicable Diseases Towards Healthy and Ready Meal Products: A Mixed-Methods Research - Sireerat Sooampon; Sutti Sooampon (My University, 2024)
Introduction Healthy diets reduce the risk of several non-communicable diseases (NCDs) from diabetes to heart disease and hypertension to cancer. Given their busy lifestyles, it is difficult for individuals to routinely prepare healthy food. Therefore, healthy and ready meal products have been developed and commercially launched in Thailand. Objectives Considering ready and healthy meals as an innovative product line in the Thai market, the aim of this study was to identify the factors that influence NCD patients to adopt this product innovation. Methods This study used a mixed-methods approach based on Roger's model of innovation adoption. Two hundred and twenty NCD patients completed a questionnaire regarding their expectations towards healthy meal products. In-depth interviews were conducted with 20 respondents to explore the underlying reasons behind their scoring decisions in the questionnaires. Results The findings revealed that the highest rated items were the expectation that healthy meals reduce the severity of disease, help avoid high-cholesterol food, and comprise a variety of meal choices. Instead of celebrity marketing and corporate branding, the patients preferred healthy meals that are recommended by health professionals and produced by university research teams. The qualitative findings also demonstrated that most patients welcomed healthy menus as a preventive treatment, but still have concerns regarding the availability and quality of the products. Conclusion This study reveals the expectations of prospective consumers, specifically NCD patients, towards healthy and ready meal products. It adds key information for food producers, health professionals, and policymakers to foster healthy food innovation, especially in the context of emerging economies like Thailand where healthy food choices are limited.
Keywords: Healthy food; Non-communicable disease; Consumer Attitudes and Food Labeling